(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
The Municipal Solid Waste (Management and Handling) Rules 2000 give that the Municipal Authority or an administrator of an office will get authorisation for setting up of Waste Processing and Disposal office including landfills from the Board. The Rules additionally give the technique to be embraced by the experts for appropriate capacity, accumulation, isolation, handling, transportation and last transfer of city strong waste.